(untitled) (Communications in Computational Physics, 2018)
In this paper we propose an extremum-preserving iterative procedure for the imperfect interface problem. This method is based on domain decomposition method. First we divide the domain into two sub-domains by the interface, then we alternately solve the sub-domain problems with Robin boundary condition. We prove that the iterative method is convergent and the iterative procedure is extremum-preserving at PDE level. At last, some numerical tests are carried out to demonstrate the convergence of the iterative method by using a special discrete method introduced on sub-domains.